Uncertainty and Sensitivity Analysis of Significant Parameters for Superlarge Diameter Shield Excavation. (23rd February 2021) - Chen, Elton J.; Chen, Yang-Yang; Wei, Lin-Chun; Luo, Han-Bin
Abstract : Excavation of a superlarge diameter tunnel by tunnel boring machine (TBM) is different from that of a shield tunnel with normal dimension, in which the control system of the superlarge TBM is very complicated and difficult to operate. Hence, it is very important to focus on the control and management of significant parameters to ensure excavation stability under uncertainty. In this paper, we (i) utilize a BIM-based big data platform (BIM-BDP) to manage the essential construction data of tunnel project in digital format; (ii) adopt the global sensitivity analysis (SA) to recognize significant parameters for shield excavation based on polynomial chaos expansion (PCE)–extended Fourier amplitude sensitivity test (eFAST) model; and (iii) employ the uncertainty analysis (UA) to discover the correlation between significant parameters from the data of the BIM-BDP. This research contributes to (i) the body of knowledge of proposing a more appropriate research methodology that can cope with aleatory and epistemic uncertainty and support uncertainty and sensitivity analysis (UA/SA) processes based on data from BIM-BDP and (ii) the state of practice by providing a data-driven surrogate model to simulate system behaviors of shield excavation with high reliability and to reduce dependency on domain experts. Here, we pay close attention to the most influential parameters that require priority parameter control, which can help administrators optimize the management of shield parameters during tunnel excavation.